Fifty freakin' years with the fabulous Furry Freak Brothers - Shelton, Gilbert 1940- (Knockabout, 2017)
"It is 50 years since the world's best-loved and best-known underground comic characters first appeared in The Rag in Austin Texas. Now published in 16 languages and with global sales of over 40 million copies. This souvenir extravaganza contains brand new strips including: Phineas Becomes a Suicide Bomber, Franklin Got His Gun and Fat Freddy Gets Religion. Gilbert Shelton has written a 6,000 word autobiography/history/anecdote-filled account of those Fifty years. Also [includes] a gallery of Freak Brothers parody strips by celebrated underground cartoonists from around the World, illustrations, posters, album covers, merchandise and lots and lots and lots more."--Supplied by publisher
Keywords: Fabulous Furry Freak Brothers (Fictitious characters) / Comic books, strips, etc; Underground comic books, strips, etc / United States; Hippies / Comic books, strips, etc; Fabulous Furry Freak Brothers (Fictitious characters); Hippies; Underground comic books, strips, etc; United States; Comic books, strips, etc; Comic